2008
DOI: 10.1007/s00417-008-0836-1
|View full text |Cite
|
Sign up to set email alerts
|

Macular corneal dystrophy: mutational spectrum in German patients, novel mutations and therapeutic options

Abstract: Different genotypes imply several phenotypes, which influence therapeutical proceedings in MCD patients. Our study shows the wide range of diagnostic findings and therapeutical options in patients suffering from macular corneal dystrophy depending on the genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
(38 reference statements)
1
11
1
Order By: Relevance
“…When considering clinical course of the disease, there were noticeable differences among patients including the age of onset (ranged from first to third decade), best corrected visual acuity (ranged from 0.05 to 0.5) and the age of therapeutic procedures (20 eyes which underwent pk out of 48 analysed eyes—41.66%). This clinical course variability was reported previously for MCD patients 8 9 18…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…When considering clinical course of the disease, there were noticeable differences among patients including the age of onset (ranged from first to third decade), best corrected visual acuity (ranged from 0.05 to 0.5) and the age of therapeutic procedures (20 eyes which underwent pk out of 48 analysed eyes—41.66%). This clinical course variability was reported previously for MCD patients 8 9 18…”
Section: Resultssupporting
confidence: 86%
“…Compound heterozygosity for L200R and R205Q and compound heterozygosity for L200R and C165Y have been reported only in patients originating from a Czech population 16. A frameshift mutation 1734_1735delTG, an R211G, and one with two compound heterozygous mutations L200R, an L173F and an additional polymorphism R162G were identified in German patients and not reported among Polish or Czech populations 9. The mutations Y110C and P64L revealed during this study in Polish patients were not previously reported neither for German or Czech patients.…”
Section: Resultscontrasting
confidence: 45%
See 2 more Smart Citations
“…Previous studies have revealed that frameshift mutations of CHST6 gene may lead to severe MCD phenotypes with much deeper grey white deposits [30].…”
Section: Discussionmentioning
confidence: 99%